THE LOGICO-SEMANTIC RELATION OF STUDENTSâ PRESENTATION IN ACCELERATION PROGRAM OF SMA LABSCHOOL JAKARTA - Sulistyaningrum, Siti Drivoka; Rasyid, Yumna (INTERNATIONAL JOURNAL OF LANGUAGE EDUCATION AND CULTURE REVIEW, 2015)
This study aims at investigating the kinds of taxis and logico-semantic relation of studentsâ presentation in Acceleration Program of SMA Labschool Jakarta. The meanings represented in clause complexes are analyzed based on the concept of relationship between clauses suggested by Halliday (1994: 373). The analysis of taxis and logico-semantic relation is necessary in order to present a pattern of the complexity of the acceleration students. The observation video was recorded in class K-12 then transcribed and analyzed by means of analysis of clause complexes proposed by Gerot and Wignell (1994: 21). The finding in the study shows that the clause complexity in the acceleration studentsâ presentation is varied. In the first group consisting 4 female students, almost all kinds of taxis and logico-semantic are relation found in their presentation, except hypotactic extension. In correspondence with the first group, the second group consisting 4 male students, has produced all kinds of relation except locution. From all groups the type of taxis and logico-semantic relation mostly arises is paratactic elaboration. The analysis of meaning reveals that the dominant meaning is addition which appears from extension.